Die Sprachwissenschaft: Ihre Aufgaben, Methoden und bisherigen Ergebnisse - von der Gabelentz, Georg; McElvenny, James; Ringmacher, Manfred (Classics in Linguistics, 2016)
"""Die Sprachwissenschaft"" is the magnum opus of the German sinologist and linguist Georg von der Gabelentz (1840-1893), a late 19th-century representative of the Humboldtian tradition of linguistic research. The book exists in two versions: a first edition of 1891 and a second posthumous edition of 1901, revised and expanded by Albrecht Graf von der Schulenburg (1865-1902), a nephew and pupil of Gabelentz. This critical edition presents for the first time the text of the two editions in a form that allows them to be easily compared. It represents a valuable resource for historiographical research into linguistics on the eve of the 20th century. "